Anatomi Daun dan Ranting Citrus nobilis L. var. microcarpa yang Terserang Citrus Vein Phloem Degeneration - Riza Linda, Heni Susanti, Mukarlina (Universitas Tanjungpura, 2014)
Citrus Vein Phloem Degeneration (CVPD) is one of the diseases that cause a decrease in the production of the Citrus nobilis L. var. microcarpa. The CVPD disease is caused by the Liberibacter asiaticus bacteria and transmitted through by psyllid (Diaphorina citri). The infected C. nobilis L. var. microcarpa indicates morphological changes which can be divided into mild, moderate, and severe symptoms. The main purpose of this research was investigating citrus leaf and twig anatomy which was infected by CVPD. The research was conducted from February 2014Â until August 2014. Paraffin method was used to make cross section sample preparation of the citrus leaf and twig. The result on cross section of leaves, petioles, and twig CVPD symptomatic indicated there was cell wall thickening on epidermis. Mesophyll (leaf) and cortexs (petioles and twig) shape changes and there is an acumulationÂ of starch. The Phloem on leaves, petioles, and twigs indicated changes in cell shape in which itÂ becomes abnormal then damage (necrosis) occured.